LGBT Youth in America's Schools - Cianciotto, Jason (University of Michigan Press, 2012)
Jason Cianciotto and Sean Cahill, experts on lesbian, gay, bisexual, and transgender public policy advocacy, combine an accessible review of social science research with analyses of school practices and local, state, and federal laws that affect LGBT students. In addition, portraits of LGBT youth and their experiences with discrimination at school bring human faces to the issues the authors discuss.